ANALISIS KOMPARATIF USAHATANI JAGUNG VARIETAS BISI 18 DAN VARIETAS PIONEER P27 GAJAH DI DESA REMBITAN KECAMATAN PUJUT KABUPATEN LOMBOK TENGAH - Wiliya, Juli; Ibrahim, Ibrahim; Septiadi, Dudi (JURNAL AGRIMANSION, 2023)
This research aims to compare production costs, production quantities, income and farming efficiency of corn variety Bisi 18 and corn variety Pioneer P27 Gajah in Rembitan Village, Pujut District, Central Lombok Regency. This research uses a descriptive method. The unit of analysis is the Bisi 18 variety corn farming and Pioneer P27 Gajah corn variety in Rembitan Village, Pujut District, Central Lombok Regency. Determining the number of sample respondents for corn variety Bisi 18 and corn variety Pioneer P27 Gajah using "quota sampling" namely by assigning 50 farmers each - 25 farmers of corn variety Pioneer P27 Gajah and 25 farmers corn variety Bisi 18. To determine the number of sample farmers for each -Each hamlet was carried out using "accidental sampling". Data collection was carried out by means of a survey, namely direct interviews with respondents using a questionnaire tool. The data analysis used is cost analysis, income analysis, efficiency analysis and comparative analysis using the T-test. The results of this research are that the average production cost of the Pioneer P27 Gajah corn farming is IDR 10,252,563/ha and the production cost of the Bisi 18 corn variety is IDR 11,647,466/ha. The average production on the Pioneer-27 Gajah corn variety farm is 4,685 kg/ha, while the production on the Bisi 18 variety corn farm is 5,360 kg/ha. The average farming income for the Pioneer-27 Gajah corn variety is IDR 12,317,908/ha, while for the Bisi 18 corn variety it is IDR 14,324,472/ha. The efficiency of corn farming of the Bisi 18 variety is 2.23, which is greater than the efficiency of corn farming of the Pionerr-27 Gajah variety, namely 2.20.